2016
DOI: 10.1177/0018720816640394
|View full text |Cite
|
Sign up to set email alerts
|

Flying the Needles

Abstract: Long-haul crews have to be supported in a timely manner by adequate training tailored to address manual skills or by operational provisions like mixed-fleet flying or more frequent transitions between short-haul and long-haul operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…However, the usage of occlusion allows for a more systematic analysis of information processing under restricted conditions. The observed flightpath deviations show similar amplitudes compared to other flight simulator studies (Ebbatson et al 2010;Haslbeck and Hörmann 2016), thus indicating that the occlusion conditions in this study did affect the participants but did not lead to a complete failure in the manual flying task (Table 6). Thus, occlusion appears as an approach to generate valid data to analyze pilots' performance under conditions of restricted visual resources (see Gray et al 2008).…”
Section: Discussionsupporting
confidence: 79%
“…However, the usage of occlusion allows for a more systematic analysis of information processing under restricted conditions. The observed flightpath deviations show similar amplitudes compared to other flight simulator studies (Ebbatson et al 2010;Haslbeck and Hörmann 2016), thus indicating that the occlusion conditions in this study did affect the participants but did not lead to a complete failure in the manual flying task (Table 6). Thus, occlusion appears as an approach to generate valid data to analyze pilots' performance under conditions of restricted visual resources (see Gray et al 2008).…”
Section: Discussionsupporting
confidence: 79%
“…A false alarm confused three participants in the no-attack group causing them to decide incorrectly about when to turn. This might indicate that navigational tasks are already severely challenging some pilots because they are flying their aircraft normally with flight-director and autopilot engaged (Haslbeck and Hoermann, 2016). Raw data flying-flying according to the needles-seems to challenge some of the pilots even without any further tasks, but especially when confronted with a secondary task such as verifying their instruments in an ambiguous, unexpected situation.…”
Section: Performance (Rq 7 and Rq 8)mentioning
confidence: 99%
“…Coming from the human factors domain, we favor the distinction from Firesmith (2003, p. 2) who defines safety as "the degree to which accidental harm is prevented, detected, and properly reacted to." Common safety issues might arise in the context of fatigue (Caldwell, 2012;Rosekind et al, 1994), loss of manual flying skills (Haslbeck and Hoermann, 2016), complex task switching (Gontar et al, 2017a,b), or technical malfunctions involving effortful problem solving and decision-making (Mosier and Fischer, 2010;Orasanu and Fischer, 2014) as well as intense team-communication (Gontar et al, 2017a,b). Firesmith (2003, p.14) defines security as "the degree to which malicious harm to a valuable asset is prevented, detected, and reacted to."…”
Section: Introductionmentioning
confidence: 99%
“…This missing learning channel might also be affecting currency levels of passive sidestick pilots. Research done by Haslbeck & Hoerman [18] showed a difference in manual flying skill degradation between long-haul pilots and short-haul pilots. They concluded that the difference lies in the lack of practice of long-haul pilots, who only are only conducting a few flights a month.…”
Section: Unlinked Flight Controls On Flying Skill Developmentmentioning
confidence: 98%